Mystery and magic realism in The Distance Between Us and the Perfect World of Miwako Sumida: A comparative literary analysis - Ngestirosa Endang Woro Kasih, Elisabeth; Wulandari, Anggi (EduLite: Journal of English Education, Literature and Culture, 2025)
This study scrutinizes the magical realism in Reyna Grande's The Distance Between Us and Clarissa Goenawan's The Perfect World of Miwako Sumida through the four characteristics of Wendy B. Faris: the irreducible element, the phenomenal world, the unsettling doubt, and the merged nature. This study was under a descriptive qualitative research design to explore the presence and function of magical realism and mystery. The qualitative approach was designated to allow a deeper understanding of how narrative elements contribute to emotional resonance and ambiguity in literary texts. The primary data sources were the two novels under study. Selected narrative passages and dialogues that exhibit characteristics of magical realism and mystery were identified for analysis. The study used content analysis with a thematic analytical framework supported by a comparative literary analysis. Data were scrutinized using Wendy B. Faris’s four characteristics of magical realism. Findings show that in Goenawan's novel, ghost sightings and surreal events build a mysterious atmosphere which challenges the boundaries of reality. While in Grande's work, El Otro Lado is present as an invisible force that is full of mystery, creating doubt and emotional tension. Both works display how magical realism and mystery work together to discover complex inner experiences and jiggle the boundaries between reality and unconscious. Future scholars are encouraged to figure on these findings by discovering how magical realism encounters with trauma theory, identity formation, or diasporic narratives across diverse cultural contexts.